2011
DOI: 10.1186/1756-0500-4-353
|View full text |Cite
|
Sign up to set email alerts
|

Cause of death among Ghanaian adolescents in Accra using autopsy data

Abstract: BackgroundThere is limited data on adolescent mortality particularly from developing countries with unreliable death registration systems. This calls for the use of other sources of data to ascertain cause of adolescent mortality. The objective of this study was to describe the causes of death among Ghanaian adolescents 10 to 19 years in Accra, Ghana utilizing data from autopsies conducted in Korle Bu Teaching Hospital (KBTH).FindingsOut of the 14,034 autopsies carried out from 2001 to 2003 in KBTH, 7% were am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…These include, among others, the poor or non-existent acceptability of the typical and highly disfiguring CDA procedure, the lack of pathology expertise and infrastructure in low-resource regions, and the fact that in such settings the majority of deaths occur outside of formal health system premises [1,2]. The practice of the CDA is therefore restricted to research projects, forensic investigations for medico-legal purposes, and deaths reaching referral hospitals in the few countries that have functional pathology services capable of routinely performing autopsies [35]. As a consequence of such challenges, the use of less invasive post-mortem sampling techniques, such as the minimally invasive autopsy (MIA), is being considered as a potential substitute for the CDA [68].…”
Section: Introductionmentioning
confidence: 99%
“…These include, among others, the poor or non-existent acceptability of the typical and highly disfiguring CDA procedure, the lack of pathology expertise and infrastructure in low-resource regions, and the fact that in such settings the majority of deaths occur outside of formal health system premises [1,2]. The practice of the CDA is therefore restricted to research projects, forensic investigations for medico-legal purposes, and deaths reaching referral hospitals in the few countries that have functional pathology services capable of routinely performing autopsies [35]. As a consequence of such challenges, the use of less invasive post-mortem sampling techniques, such as the minimally invasive autopsy (MIA), is being considered as a potential substitute for the CDA [68].…”
Section: Introductionmentioning
confidence: 99%
“…[10] There is scarce data on prevalence of NCDs among children in Ghana. However, a study conducted by Agyemang et al (2005) among children aged [8][9][10][11][12][13][14][15][16] in the Ashanti Region showed that blood pressure increased with increasing age. Results from the study further showed that rural boys had a lower systolic and diastolic blood pressure than semi-urban boys and lower systolic blood pressure than urban boys.…”
Section: Introductionmentioning
confidence: 99%
“…[13] A study by Ohene et al (2009), examining autopsy cases at the Korle Bu Teaching Hospital in Ghana revealed that 41% of adolescents aged 10-19 years died of NCDs. [14] These initial facts underscore the urgent need for public health measures to prevent increasing prevalence of NCDs from becoming a public health burden in Ghana among children or adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Mills and colleagues 44 found abortion-related causes to be the leading cause of maternal death in rural northern Ghana, as did Baiden and colleagues 10 . Ohene et al 45 discovered that the majority of adolescent maternal deaths at Korle Bu Teaching Hospital in Accra were due to complications from unsafe abortion. Abortion complications were the leading cause of death among the youngest women in a sample of maternal deaths at Tamale Teaching Hospital, and the fourth leading cause overall 45 .…”
Section: Resultsmentioning
confidence: 99%